The role of non-timber forest products in household coping strategies in South Africa: the influence of household wealth and gender - Paumgarten, F.; Shackleton, Charlie M. (2011)
The prevalence and ranking of non-timber forest products (NTFPs) as safety-nets has been well discussed, but rarely quantified. We report on group discussions and household interviews in two South African villages to assess the frequency and nature of shocks and stresses over a 2-year period and the coping strategies employed, stratified by household wealth and gender of the de jure household head. Overall, kinship was the most widely adopted coping strategy, and NTFPs were the fifth most prevalent (employed by 70% of households). There were relatively few differences in the nature of shocks or responses between male- and female-headed households. Wealth influenced the experience of shocks or stresses as well as responses. Poorer households have fewer options with the increased use or sale of NTFPs being the second most commonly adopted strategy. Increased use and sale of NTFPs is a common manifestation of the safety-net function. To reconcile long-term economic development and biodiversity conservation, it is important to understand people’s use of natural resources and the factors that affect this use, including their responses to shocks and stresses.